Use of Gram-Positive Grass Bacillus as Autonomous Repair Agent in Concrete - Nishant Kumar and Sunil Saharan (Nature Environment and Pollution Technology, 2022)
Due to various reasons, crack formation may occur in the concrete structure. Crack formation increases the permeability of concrete to detrimental substances including different types of chemicals, glasses, and water, which upon contact with concrete leads to significant impairment in various properties of concrete including strength, durability, etc. In the present investigation, special microbiological growth having the ability to precipitate calcite through the process of biomineralization is induced in the concrete to evaluate the performance of the concrete. The bacteria were directly added to the concrete mix instead of encapsulating them into clay pellets. Bacteria were classified into two groups i.e. A & B. i. e. 50 & 100 g of bacteria powder were added into 1 L of water respectively. Out of the two groups A and B, 4 samples each were taken of 10 mL, 20 mL, 30 mL and 40 mL, and mixed in the concrete. The results showed that compressive strength and flexural strength increased up to 23.57% and 35% respectively more than the control specimen and the optimum capacity achieved at 30 mL bacterial concentration.